Evaluation Of Internet Protocal Version 6 (IPV6) Implementations And Comparative Performance Analysis On Different Platforms - Syed Mohamed, Sulaiman (2005)
The main objective of this work is to investigate the IP stack performance on popular platforms such as Windows, RedHat and FreeBSD and to compare their performances so that the right platform for a specific network application can be recommended. Internet protocol version 6 (IPv6) has been chosen as target of evaluation due to its increasing popularity in recent years.